Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fneur.2014.00278
|View full text |Cite
|
Sign up to set email alerts
|

A RCT Comparing Specific Intensive Cognitive Training to Aspecific Psychological Intervention in RRMS: The SMICT Study

Abstract: Background: Specific cognitive rehabilitation in multiple sclerosis (MS) resulted to be effective compared to no treatment. So far the possible role of an aspecific psychological intervention on cognition has not been investigated.Objective: The aim of the SMICT RCT was to compare the efficacy of a specific cognitive training with an aspecific psychological intervention in relapsing-remitting MS patients.Methods: From a sample of 150 patients, with the same disability and immunomodulatory therapy, submitted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 32 publications
(38 reference statements)
1
39
0
Order By: Relevance
“…Bonavita et al [59], noted significant pre-to post treatment improvements in a RehaCom treated MS cohort, on mental information processing, executive functions and attention. This and other similar studies have reported positive outcomes in MS patients treated with this software, and moreover, associations between functional neuroimaging (f-MRI) findings with changes in neurocognitive measures have been reported [59][60][61]. In a multicenter Italian study, RehaCom was utilized to provide specific intensive cognitive training for 12 months.…”
Section: Cognitive Neurorehabilitation In Multiple Sclerosismentioning
confidence: 79%
“…Bonavita et al [59], noted significant pre-to post treatment improvements in a RehaCom treated MS cohort, on mental information processing, executive functions and attention. This and other similar studies have reported positive outcomes in MS patients treated with this software, and moreover, associations between functional neuroimaging (f-MRI) findings with changes in neurocognitive measures have been reported [59][60][61]. In a multicenter Italian study, RehaCom was utilized to provide specific intensive cognitive training for 12 months.…”
Section: Cognitive Neurorehabilitation In Multiple Sclerosismentioning
confidence: 79%
“…[125][126][127][128][129][130][131] Restitutive cognitive training is aimed at directly treating the impaired function and should be deficit-specific. 132,133 On the other hand, learning compensatory strategies indirectly treats impaired functions. For example, the MEMREHAB (Memory Rehabilitation) trial, 134 a recent RCT not included in the two Cochrane reviews mentioned above, showed that teaching the systematic use of context information and visual imagery over 10 sessions facilitated the acquisition of new verbal information in a group of patients with clinically definite MS, not only in neuropsychological tests, but also in everyday situations.…”
Section: Treatmentmentioning
confidence: 99%
“…For example, the efficacy of exercise training and cognitive rehabilitation interventions on walking and cognition might differentially depend on clinical characteristics, such as disability status 80 or domain of cognitive impairment. 65,75 Nevertheless, there is much that can be learned from the gerontology literature and applied in a novel manner for managing cognitive and motor outcomes independently and collectively using exercise training and cognitive rehabilitation in MS.…”
Section: Cognitive-motor Coupling and Cross-modality Transfer Effectsmentioning
confidence: 99%